Deciphering the microbial diversity associated with healthy and wilted Paeonia suffruticosa rhizosphere soil - Jia, Manman; Sun, Xin; Chen, Man; Liu, Shuang; Zhou, Jinxing; Peng, Xiawei (Frontiers in Microbiology, 2022)
Plant health is closely related to the soil, where microorganisms play a critical and unique role. For instance, Paeonia suffruticosa is an emerging woody oil crop in China with attractive development and utilization prospects. However, black root rot causes wilting of the aboveground plant parts, which significantly affected its seed yield and quality. Studies found that soil microorganisms are critical in maintaining plant health, but how changes in the soil microbial communities affect the healthy and diseased oil peony is unclear. Therefore, our present study used high throughput sequencing and BIOLOG to analyze the rhizosphere soil microbial communities of healthy and diseased oil peonies. Our results revealed that the physical and chemical properties of the soil of the diseased plants had changed, with the ability to metabolize the carbon source being enhanced. Moreover, our research highlighted that the oil peony-infecting fungal pathogenic genus (Fusarium, Cylindrocarpon, and Neocosmospora) was closely associated with oil peony yield reduction and disease aggravation. Further network analysis demonstrated that the bacterial and fungal networks of the diseased plants were more complex than those of the healthy plants. Finally, the inter-kingdom network among the diseased plants further indicated that the lesions destroyed the network and increased the intraspecific correlation between the fungal groups.